A metabolomic approach to understand the solid-state fermentation of okara using Bacillus subtilis WX-17 for enhanced nutritional profile - Mok, Wai Kit (2019)
Okara is a major agro-waste produced from the soybean industry. To hydrolyze the okara and enable nutrient release, a strategy to valorize okara using solid-state fermentation with food grade Bacillus subtilis (B. subtilis) WX-17 was carried out. The study showed that fermentation of okara with B. subtilis WX-17 improved its overall nutritional content. The total amino acids content increased from 3.04 ± 0.14 mg/g in unfermented okara to 5.41 ± 1.21 mg/g in okara fermented with B. subtilis WX-17. Total fatty acids content increased from 153.04 ± 5.10 to 166.78 ± 2.41 mg/g okara, after fermentation. Antioxidant content (DPPH) also increased by 6.4 times after fermentation. To gain insight into the mechanism, gas chromatography–mass spectrometry analysis was carried out. In total, 49 metabolites were detected, which could be classified mainly into carbohydrates, TCA cycle metabolites, amino acids and fatty acids. The decrease in carbohydrate metabolites, showed that glycolysis was upregulated. This would have provided the energy and metabolic flux towards the amino acid and fatty acid pathway. This is also in line with the increased amino acids and fatty acid production seen in okara fermented with B. subtilis WX-17. The findings of this work demonstrated the potential of using B. subtilis WX-17 fermentation, to enhance the nutritional profile of okara. This could serve as a potential low-cost animal feed or incorporated into the human diet.